Coping Strategies in Overcoming Fear of Missing Out in Early Adulthood: A Study of Active Social Media Users - Muhammad Egy Andara; Dedy Surya; Millatina Mukhtarullah (UIN Sunan Gunung Djati Bandung, 2026)
Digital technology has transformed communication and social interaction, especially among Indonesia's largest social media user demographic, young adults. This excessive use typically causes fear of missing out (FoMO), a persistent anxiety about missing out on crucial information or online activities. Despite FoMO's negative effects on mental health, most Indonesian literature uses static quantitative-correlational approaches, leaving a research gap on how young adults actively develop subjective coping strategies, especially those that incorporate local spiritual values. This phenomenological qualitative study examines coping processes to overcome modern anxiety. Six active IAIN Langsa student social media users with high digital anxiety were sampled using purposive sampling. In-depth semi-structured interviews, participant observation of motor anxiety, and screen time and electronic transaction history analysis were used to collect data. Young adults utilize PFC in the form of digital detox and screen time management and EFC in the form of positive reappraisal. Religious-spiritual coping like prayer, dhikr, and internalizing qana'ah (sufficiency) and tawakkal are key to neutralizing digital social pressures and restoring mental health. This study suggests holistic psychosocial and digital literacy interventions for young adults in the hyperconnected era using the FOMO-Qana'ah Dialectic Framework paradigm.